Hallen für Neue Kunst Schaffhausen : Kurzführer zu den ausgestellten Werken =. - Feurer, Thomas; Raussmüller, Urs; Wenger, Marcel; van Lil, Kira; Hallen für Neue Kunst, Schaffhausen (Ostfildern-Ruit : Hatje Cantz Verlag, 1999)
Andre, Carl ; Beuys, Joseph ; Riverhead (New York) ; Judd, Donald ; Kounellis, Jannis ; LeWitt, Sol ; Long, Richard ; Mangold, Robert ; Merz, Mario ; Nauman, Bruce ; Ryman, Robert ; Weiner, Lawrence
biog. per kunstenaar
Duits & Engels
boek